2024
DOI: 10.5132/eec.2018.01.02
|View full text |Cite
|
Sign up to set email alerts
|

Estrogenicity and cytotoxicity of sediments and water from the drinkwater source-basin of Montevideo city, Uruguay

Abstract: Frequently new pollutants are released into the environment, demanding the employment of generic methods to detect toxic responses. In vitro bioassays such as the yeast estrogenicity screening (YES) allow detecting estrogenic and citotoxic compounds avoiding the employment of invasive methods. We determined the cytotoxicity and estrogenic activity in sediments of the Santa Lucia River Basin (Uruguay) using YES assay and the association with land uses and parameters of water quality and sediment. Water quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
1

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
2
4
0
1
Order By: Relevance
“…The estrogenic activities detected herein for Guanabara Bay sediments were close to those reported at the Santa Lucia Basin, ranging from non‐detected (ND) to 8.49 ngg −1 (Griffero et al., 2018), corroborating the relationship between estrogenicity and urban‐industrial land use postulated by those authors and other literature assessments (Griffero et al., 2018; Maloney et al., 2023). Studies in other countries have reported variable values, such as in samples from the Rhine River in Germany, which ranged from 1.03 to 5.14 ng g −1 (Schulze‐Sylvester et al., 2016).…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…The estrogenic activities detected herein for Guanabara Bay sediments were close to those reported at the Santa Lucia Basin, ranging from non‐detected (ND) to 8.49 ngg −1 (Griffero et al., 2018), corroborating the relationship between estrogenicity and urban‐industrial land use postulated by those authors and other literature assessments (Griffero et al., 2018; Maloney et al., 2023). Studies in other countries have reported variable values, such as in samples from the Rhine River in Germany, which ranged from 1.03 to 5.14 ng g −1 (Schulze‐Sylvester et al., 2016).…”
Section: Resultssupporting
confidence: 89%
“…The estrogenic activities detected herein for Guanabara Bay sediments were close to those reported at the Santa Lucia Basin, ranging from non-detected (ND) to 8.49 ngg −1 (Griffero et al, 2018), activity in sediments from five sampling stations at Tokyo Bay, indicating the highest estrogenic activity of 84.3 ng g −1 near a wastewater treatment plant. The highly variable detections observed in Guanabara Bay sediment samples were also noted at Maluan Bay, (Wang et al, 2015), which may be associated with issues here in to complex environmental matrices, influenced by different contamination mechanisms, as well as such as estrogenic compound circulation, redistribution, and deposition and tidal hydrodynamics, among others (Wang et al, 2015) Analyzing sediments from Guanabara Bay is a very complex task, due to the influence of frontal systems and the speed of tidal currents that generate turbulence, resulting from the local bathymetry and the narrowing Bay entrance, which can influence the response of each collected point (Kjerfve et al, 1997;JICA, 1994).…”
Section: The Saccharomyces Cerevisiae Yeast Used In the Yes Assay Giv...supporting
confidence: 80%
See 2 more Smart Citations
“…Mais recentemente, verificou-se a estrogenicidade em diversos rios da China, e observaram-se baixas e altas concentrações, com valores que variaram de 0,01 a 40,27 ng.L -1 em águas superficiais (YAO et al, 2018). E no Uruguai, segundo o estudo realizado por Griffero et al (2018) na matriz aquática do rio Santa Lucía, observou-se um EQ-E2 de 2,4 ng.L -1 em apenas um dos três pontos analisados, no mês de janeiro.…”
Section: Atividade Estrogênica Pelo Ensaio Yeast Estrogen Screenunclassified